Sustainable Urban Environments An Ecosystem Approach - van Bueren, Ellen M.; van Bohemen, Hein.; Itard, Laure; Visscher, Henk.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
The urban environment – buildings, cities and infrastructure – represents one of the most important contributors to climate change, while at the same time holding the key to a more sustainable way of living. The transformation from traditional to sustainable systems requires interdisciplinary knowledge of the re-design, construction, operation and maintenance of the built environment. Sustainable Urban Environments: An Ecosystem Approach presents fundamental knowledge of the built environment. Approaching the topic from an ecosystems perspective, it shows the reader how to combine diverse practical elements into sustainable solutions for future buildings and cities. You’ll learn to connect problems and solutions at different spatial scales, from urban ecology to material, water and energy use, from urban transport to livability and health. The authors introduce and explore a variety of governance tools that support the transformation process, and show how they can help overcome institutional barriers. The book concludes with an account of promising perspectives for achieving a sustainable built environment in industrialized countries. Offering a unique overview and understanding of the most pressing challenges in the built environment, Sustainable Urban Environments helps the reader grasp opportunities for integration of knowledge and technologies in the design, construction and management of the built environment. Students and practitioners who are eager to look beyond their own fields of interest will appreciate this book because of its depth and breadth of coverage.
1. Introduction. 1.1 The built environment: problem and solution. 1.2 Analysing the urban environment: an ecosystem approach. 1.3 Analytical focus is on ecological processes. 1.4 Setting the boundaries in this book; E. van Bueren -- 2. (Eco)system thinking: ecological principles for buildings, roads, industrial and urban areas. 2.1 Introduction. 2.2 General characteristics of (eco)system thinking. 2.3 The development of system theory and ecosystem theory. 2.4 Important concepts and characteristics of ecosystems. 2.5 Classification of ecosystems on different levels of scale (from global to local level) 2.6 Examples of urban-ecosystem approaches. 2.7 Understanding urban areas as ecosystems. 2.8 Improving urban systems: ecological engineering. 2.9 The earth as a living system. 2.10 Discussion; H. van Bohemen -- 3. Urban ecology, scale and identity. 3.1 Introduction. 3.2 Ecologies. 3.3 Urban ecology including the human species and its artefacts. 3.4 Scale and size: technically, scientifically, administratively. 3.5 Identity: difference from the rest, continuity in itself. 3.6 Conclusion; T.M. De Jong -- 4. Water flows and urban planning. 4.1 Introduction. 4.2 Flow issues: cycles and cascades. 4.3 Urban Spaces and the Water Cycle. 4.4 Water Planning and Innovation: the role of actors. 4.5 Conclusions; S. Tjallingii -- 5. Energy in the built environment. 5.1 Introduction. 5.2 The energy chain: from demand to supply. 5.3 Demand side: Thermal energy demand. 5.4 Demand side: Electrical energy demand of buildings. 5.5 Energy distribution: between supply and demand. 5.6 Supply side: Energy conversion systems and primary energy use. 5.7 Operational and financial considerations; L. Itard -- 6. Material City: Towards sustainable use of resources. 6.1 Introduction. 6.2 Energy and materials. 6.3 Concepts. 6.4 Strategies. 6.5 Challenges. 6.6 The value of assessment tools. 6.7 Selecting materials; L. Icibaci, M. Haas -- 7. Air quality and human health. 7.1 Introduction. 7.2 Air pollutants. 7.3 Other indoor environmental aspects. 7.4 Health effects. 7.5 Practical guidelines. 7.6 Conclusions; A. Meijer -- 8. Liveability. 8.1. Introduction. 8.2 Methodology. 8.3 Forms of liveability. 8.4 The neighbourhood as an ecosystem. 8.5 Sustainable liveability. 8.6 Sustainable liveable neighbourhoods. 8.7 The Ecological liveability; control over social environment. 8.8 Reflection and conclusions; M. van Dorst -- 9. Urban transport and sustainability. 9.1 Introduction. 9.2 A conceptual model for the impacts of the transport system on the environment, accessibility and safety. 9.4 Policy measures and design. 9.5 Models. 9.6 Conclusions; B. van Wee -- 10. Sustainable Urban Form. 10.1 Introduction. 10.2 Typologies of urban form. 10.3 The policy relevance of urban form. 10.4 The Concept of the Compact City. 10.5 Urban form and environmental performance. 10.6 An assessment of urban form. 10.7 Concluding remarks; J. Milder -- 11. Environmental strategies and tools for integrated design. 11.1 Introduction. 11.2 Environmental strategies. 11.3 Quantitative assessment methods. 11.4 Qualitative assessment methods. 11.5 Design methods for integrated design; L. Itard -- 12. Climate Integrated Design and Closing Cycles. 12.1 Introduction. 12.2 Relevant references of a sustainable and interconnected energy and sanitation facility. 12.3 Integrated concepts: combined infrastructural, spatial and ecological functions. 12.4 Curitiba: integrating social and technical solutions. 12.5 Challenges for realizing a sustainable urban metabolism; A. van Timmeren -- 13. Governance tools. 13.1 Introduction. 13.2 Government and Governance. 13.3 Levels of Governance. 13.4 Governance tools. 13.5 Information and Communication Tools. 13.6 Governance Tools and Sustainable Built Environments. 13.7 Conclusions; L. Murphy et al -- 14. Managing change. 14.1 Introduction. 14.2 Challenges in the urban environment. 14.3 Theoretical understanding of managing change. 14.4 The diffusion of environmental innovations. 14.5 Improving collaboration. 14.6 Which actors can make the change? 14.7 End-user participation. 14.8 Business opportunities: sustainability pays. 14.9 Conclusions; A. van Hal, E. van Bueren -- 15. Conclusions and solutions. 15.1 Introduction. 15.2 Improving the metabolism of urban areas. 15.3 Making areas and places more sustainable. 15.4 Promising solutions; T. Schuetze et al -- Index.
Keywords: Urban ecology (Biology).; Architecture; Regional planning; Urban planning; Renewable energy resources; Water pollution; Urban Ecology; Architecture, general; Landscape/Regional and Urban Planning; Renewable and Green Energy; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution